Innovation and Technology in Korea Challenges of a Newly Advanced Economy - Mahlich, Jörg.; Pascha, Werner; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2007)
Only inadequately perceived by the Western public, Korea has transformed into an economic heavy weight during recent decades. The Korean government believes it can turn it into one of the top 10 competitive economies until 2010. This goal does not sound overambitious as Korea has undergone tremendous efforts in order to forge ahead in the field of research and development. In some high tech industries, Korean firms have advanced into leading players in the global market place and are increasingly challenging their international competitors. Against this background, the volume offers an in-depth analysis of the Korean innovation system and shows how its science and technology policies actually work. As Korea’s economy is now reaching the status of a newly advanced economy, the book also takes a close look on ongoing structural changes in the course of economic globalization.
Introduction: Korea as a Newly Advanced Economy and the Role of Technology and Innovation -- Introduction: Korea as a Newly Advanced Economy and the Role of Technology and Innovation -- General Surveys -- The Korean Innovation System: From Industrial Catch-Up to Technological Leadership? -- The Development of Technological Capability and the Transformation of Inward FDI in Korea from 1962 to 2000 -- On the Time Lag between Technology Policy and FDI Policy in Korea - A Comment on Jin-Hyo Joseph Yun’s Paper -- Paradigm Shift and Challenges for Korean Industry: Case Study of Samsung -- Cross-cutting Issues -- Corporate Governance and Investment in R&D in South Korea -- The Revolution of Auditing System in Korea -- Public-Private R&D Collaboration in Korea - A Cross-Sector Survey of Incentive Structures -- Public-Private R&D Partnerships: Current Issues and Challenges -- The Technological Competencies of Korea’s Firms: A Patent Analysis -- Korean Technological Competencies: Institutional Framework and Patterns of Industrial Competition -- Effects of Patents on the Total Factor Productivity of ICT Industry in Korea -- Comment on Keun Yeob Oh and Taegi Kim: Patents and Productivity Growth in Information and Communication Technology Industry of Korea -- Use of Technology Foresight in S&T Policy Making: A Korean Experience -- The Added Value of Technology Foresight -- Sectoral Issues -- Nanotechnology in Korea — Actors and Innovative Potential -- Korea’s Telecommunications Industry -- Keeping Pace with Globalisation: Innovation Capability in Korea’s Telecommunications Equipment Industry -- Success of CDMA Telecommunications Technology in Korea: The Role of the Mobile Triangle.
Keywords: Economic policy; Management; Industrial management; Development economics; R & D/Technology Policy; Innovation/Technology Management; Development Economics